Marine-Lenhart Syndrome: Current Perspectives on Diagnosis and Management - Alexander Kam; Yanne Pradwi Efendi; Dinda Aprilia; Eva Decroli; Syafril Syahbuddin; Suci Berlian Hemilton (Scientific Journal, 2025)
Marine-Lenhart syndrome (MLS) is an uncommon disorder characterised by the concurrent presence of Graves’ disease and hyperfunctioning thyroid nodules. Its global prevalence ranges between 2.7- 4.1% of Graves’ disease cases, presenting significant challenges in diagnosis and management. MLS is often difficult to detect due to limitations in autoimmune serology tests, thyroid ultrasonography, and access to nuclear medicine facilities. Diagnosis relies on a combination of clinical hyperthyroidism symptoms, the presence of specific thyroid antibodies, and scintigraphy findings that reveal "hot" or "cold" nodules. The primary therapeutic options for MLS include antithyroid drugs, radioactive iodine (RAI) therapy, and surgery. RAI is commonly employed as definitive treatment, often requiring higher doses to address the resistance of hyperfunctioning nodules. Surgery is indicated in cases involving large nodules, compressive symptoms, or suspected malignancies. Treatment strategies should be tailored to the individual clinical characteristics of each patient to minimize complications and ensure optimal outcomes. Advancing the diagnosis and management of MLS requires enhanced access to advanced diagnostic technologies and improved healthcare provider proficiency in identifying and treating the syndrome. A multidisciplinary and integrated approach is essential for achieving favorable clinical outcomes for MLS patients.